A novel micro-to-macro structural approach for mechanical characterization of adipose tissue extracellular matrix. (January 2018) - Seyfi, Behzad; Fatouraee, Nasser; Samani, Abbas
Abstract: Mechanical characterization of adipose tissue micro-components is important for various biomedical applications such as tissue engineering and predicting adipose tissue response to forces involved in relevant medical intervention procedures (e.g. breast needle biopsy). For this characterization, we introduce a novel structural method for micromechanical modeling of the adipose tissue. The micromechanical model was developed using fluid-structure interaction (FSI) formulation. We utilized this model within an inverse problem framework to estimate the hyperelastic parameters of adipose tissue extracellular matrix (ECM). Using this framework, the ECM hyperelastic parameters were changed in the FSI model systematically using an optimization algorithm such that the mechanical response obtained from the FSI model matches the corresponding experimental response reported in previous studies. To account for adipocyte size variation, the hyperelastic parameters were determined for different adipocyte sizes in the FSI model. Results obtained in this investigation indicate that at various strains under quasi-static conditions, the stiffness of adipose tissue ECM is ~ (2–3) times higher than that of the adipose tissue. The results also indicate a very good fit between the FSI model responses and their experimental counterparts. This indicates the reliability of the proposed FSI model in capturing major elements of the adipose tissue micromechanics. As such, it is potentially useful in applications such as tissue engineering, estimating tissue deformation pertaining to medical intervention and cataloging the mechanical properties of adipose tissue under health and pathological conditions. It can also be utilized as a forward model for developing inversion algorithms designed to determine pathological adipose microstructural alterations.